2012
DOI: 10.4276/030802212x13286281651153
|View full text |Cite
|
Sign up to set email alerts
|

Dance as a Complex Intervention in an Acute Mental Health Setting: A Place ‘In-Between’

Abstract: This article discusses the evaluation of a dance programme in the United Kingdom. There is little research specifically on dance within hospital-based environments. The aim was to ascertain whether dance is a useful intervention for service users in such an environment; to identify its effects on participants' inner-world experience; and to understand whether it has a positive contribution to hopefulness, as identified by Spandler et al (2007) in a national study of the effect on mental health of engaging with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…A reduction in anxiety levels was recorded by Froggett and Little () and Mouradian (). Likewise Dowrick et al.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…A reduction in anxiety levels was recorded by Froggett and Little () and Mouradian (). Likewise Dowrick et al.…”
Section: Resultsmentioning
confidence: 77%
“…A reduction in anxiety levels was recorded by Froggett and Little (2012) and Mouradian (2013). Likewise Dowrick et al (2012) reported a reduction in depressive symptoms for those with common mental health problems attending reading groups for 12 months.…”
Section: Improvements In Health and Well-beingmentioning
confidence: 90%
See 1 more Smart Citation
“…In order to cultivate versatile talents that can meet the requirements of national and social development, art education and physical and mental health have been included in the Chongqing College of Electronic Engineering, Chongqing 401331, China. E-Mail: xiayandsoe@126.com quality education as important components (Froggett & Little, 2012). Various colleges and universities have set up elective courses of folkart education and mental health education.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade a small number of studies have addressed creative activity interventions within mental health setting's including creative writing (Cooper, 2013), dance (Froggett & Little, 2012), poetry (Hilse, Griffith, & Corr, 2007) and the use of clay (Timmons & MacDonald, 2008). Other research has been more broadly concerned with a range of creative activities including: painting, drawing, collage, card making, textiles, needlecraft, pottery and woodwork (Griffith, 2008;Lloyd, Wong, & Petchkovsky, 2007;Schmid, 2004).…”
Section: Introductionmentioning
confidence: 99%